Identifying key covariates of clinical outcomes for critically ill patients with Parkinson’s disease: analysis of the MIMIC-IV database - LiHua Luo; Yang Chen; HangQing Zhao; HangQing Zhao; Rong Dong; Rong Dong; Yuzhou Long (Frontiers in Neurology)
BackgroundParkinson’s disease (PD) is a common chronic degenerative disease, and its exact pathological mechanism remains unclear. In this study, we identified covariates associated with the clinical outcomes of PD using patient data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, providing new references for the treatment of patients.MethodsThe data of patients with PD and relevant covariates were obtained from the MIMIC-IV database. The patients were categorized into the in-hospital death and in-hospital survival groups based on their survival status, and the relationship between their outcomes and covariates was investigated. Key covariates markedly associated with the clinical outcomes of PD were further screened using regression analysis. Finally, a nomogram for predicting the risk of in-hospital mortality in patients with PD was constructed and validated.ResultsA total of 143 patients with PD and 37 covariates were included in this study. Of the included patients, 25 were assigned to the in-hospital death group and 118 were assigned to the in-hospital survival group. Covariates such as the respiratory rate, mean arterial pressure (MAP), respiratory failure, anion gap, bicarbonate levels, blood urea nitrogen levels, and sequential organ failure assessment (SOFA) scores were markedly associated with in-hospital mortality in patients with PD. Subsequently, age [hazard ratio (HR) = 1.0565, 95% confidence interval (CI) = 1.0065–1.1090, p < 0.05], bicarbonate levels (HR = 0.8988, 95% CI = 0.8310–0.9722, p < 0.05), BUN levels (HR = 1.0292, 95% CI = 1.0084–1.0503, p < 0.05), and SOFA scores (HR = 1.1510, 95% CI = 1.0324–1.2831, p < 0.05) were identified as key covariates associated with in-hospital mortality. The nomogram incorporating these covariates exhibited favorable performance in predicting the risk of in-hospital mortality in patients with PD.ConclusionThis study revealed four key covariates associated with the clinical outcomes of PD, providing new references for the treatment of patients.